The 15-minute cities concept applied to a Brazilian neighborhood: case study of the cidade universitária Pedra Branca neighborhood in Palhoça-SC - Cargnin, Marcela Juliana; Marino, Cintia de Castro; Silva, Thaísa Leal da (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Although the concept of 15-minute cities may be considered recent, when looking at the history of urban planning it is possible to recognize the trajectory of different paradigms that underpin it. In 2016, Carlos Moreno defined the "15-minute City" as an urban territory where inhabitants can access all their daily needs within a 15-minute walk, making it possible to live, work and access leisure spaces within a comfortable walking radius. In this context, this article aims to apply the concept of "15-minute city" in the analysis of a Brazilian neighborhood. To this end, firstly, the concept is understood through a literature review that covers theoretical and conceptual reflections on the works of authors such as Ebenezer Howard, Clarence Perry, Jane Jacobs, Gordon Cullen, among others. After the literature review, a case study of the Pedra Branca University City neighborhood in the municipality of Palhoça-SC is presented, analyzing it in light of the 15-minute City concept. Finally, this article reinforces the idea that establishing principles that reorganize urban space, mainly at the local scale of neighborhoods, as places of complex social interactions that can result in a city with a higher quality of life.